Algebra Formulas - বীজগণিত সুত্র সমূহ

✪✪✪ Algebraic Formulas | Algebraic Expression ✪✪✪
  1.    (a + b)2 = a2 + 2ab + b2
  2.    (a - b)2 = a2 - 2ab + b2
  3.    (a + b)2 = (a - b)2 + 4ab
  4.    (a - b)2 = (a + b)2 - 4ab
  5.    (a + b+ c)2 = a2 + b2 + c2 + 2ab +2bc + 2ca
  6.    (a + b+ c)2 = a2 + b2 + c2 - 2ab +2bc - 2ca
  7.    (x + a)(x + b) = x2 + (a + b)x + ab
  8.    a2 + b2 = (a + b)2 − 2ab
  9.    a2 + b2 = (a - b)2 + 2ab
  10.    a2 + b2 = $\frac{(a + b)^{2} + (a - b)^{2}} {2}$
  11.    2(a2 + b2 )= (a + b)2 + (a - b)2 
  12.  a2 + b2 + c2 =(a + b+ c)2 - 2(ab +bc + ca)
  13. 2(ab +bc + ca) = (a + b+ c)2 -  (a2 + b2 + c2 )
  14. a2 ‑ b2 = (a - b)2 + 2ab
  15.  a2 ‑ b2 = (a + b) (a - b)
  16. 4ab = (a +b)2 – (a – b)2
  17. ab = $\frac {(a + b)^{2} - (a - b)^{2}} {4}$
  18. (a + b)3 = a3 + 3a2b + 3ab2 + b3
  19. (a - b)3 = a3 - 3a2b + 3ab2 - b3
  20. (a3 + b3) = (a + b)3 – 3ab (a + b)
  21. (a3 – b3) = (a - b)3 + 3ab (a - b)
  22. (a3 + b3) = (a + b) (a2 - ab + b2)
  23. (a3 - b3) = (a - b) (a2 + ab + b2)
📗 Download as PDF

💎Download as Picture

Made By Sbook99


Thank You for Reading
Share:

Popular

Labels Cloud

Recent Posts

Subscribe by Email